Semiotic Analysis about Working Life Representation through Satire Humor in Instagram @lokerserem - Fika Faradhila; Adi Nugroho; Muhammad Husna Hisaba (Soegijapranata Catholic University, 2026)
This study attempts to explore the use of satire humor by narrowing down the representation of working life in modern culture. By referring on Roland Barthes’ theory of semiotics, this study elaborates the denotative, connotative, and myths components in the satire humor from Instagram account @lokerserem. This satire humor criticizes social issues including toxic leadership, mental exhaustion, and working exploitation in an entertaining way. This study employs qualitative approach by using secondary data from social media and literature review. The sample was chosen by considering some criterions such as the focus should be on structural issues and these contents should have high number of engagements. The findings show that satire humor can be an entertaining yet powerful tool to convey protest or critics. It is hoped that satire humor can evolve to convey people’s struggles in the workplaces more comprehensively, taking benefits as vital tool for social and cultural changes